The Effect of Good Corporate Governance, Sales Growth, and Capital Intensity on Accounting Conservatism (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2017-2019) - Fatchan Achyani; Lovita Lovita; Eskasari Putri (Universitas Muhammadiyah Surakarta, 2021)
The condition of a company must experience ups and downs that cause instability, so that conditions are different from one company to another. To attract investors and creditors as users of financial information, companies must be careful in financial reporting where companies do not rush to recognize and measure assets and profits and immediately recognize possible losses and debts. The purpose of this study is to analyze and obtain empirical evidence about the effect of good corporate governance, sales growth, and capital intensity on accounting conservatism. Indicators of good corporate governance here consist of managerial ownership, independent commissioners, audit quality, and concentrated ownership. The sample of this research is manufacturing companies in Indonesia during the 2017-2019 period which are listed on the Indonesia Stock Exchange (BEI). The results of this study indicate that independent commissioners and capital intensity have an influence on accounting conservatism.